High-density linkage map construction and QTL analysis for earliness-related traits in Gossypium hirsutum L. (December 2016) - Jia, Xiaoyun; Pang, Chaoyou; Wei, Hengling; Wang, Hantao; Ma, Qifeng; Yang, Jilong; Cheng, Shuaishuai; Su, Junji; Fan, Shuli; Song, Meizhen; Wusiman, Nusireti; Yu, Shuxun
Abstract Background Gossypium hirsutum L., or upland cotton, is an important renewable resource for textile fiber. To enhance understanding of the genetic basis of cotton earliness, we constructed an intra-specific recombinant inbred line population (RIL) containing 137 lines, and performed linkage map construction and quantitative trait locus (QTL) mapping. Results Using restriction-site associated DNA sequencing, a genetic map composed of 6, 434 loci, including 6, 295 single nucleotide polymorphisms and 139 simple sequence repeat loci, was developed from RIL population. This map spanned 4, 071.98 cM, with an average distance of 0.63 cM between adjacent markers. A total of 247 QTLs for six earliness-related traits were detected in 6 consecutive years. In addition, 55 QTL coincidence regions representing more than 60 % of total QTLs were found on 22 chromosomes, which indicated that several earliness-related traits might be simultaneously improved. Fine-mapping of a 2-Mb region on chromosome D3 associated with five stable QTLs between Marker25958 and Marker25963 revealed that lines containing alleles derived from CCRI36 in this region exhibited smaller phenotypes and earlier maturity. One candidate gene (EMF2 ) was predicted and validated by quantitative real-time PCR in early-, medium- and late-maturing cultivars from 3- to 6-leaf stages, with highest expression level in early-maturing cultivar, CCRI74, lowest expression level in late-maturing cultivar, Bomian1. Conclusions We developed an SNP-based genetic map, and this map is the first high-density genetic map for short-season cotton and has the potential to provide deeper insights into earliness. Cotton earliness-related QTLs and QTL coincidence regions will provide useful materials for QTL fine mapping, gene positional cloning and MAS. And the gene, EMF2, is promising for further study.